2007
DOI: 10.1038/sj.jid.5700481
|View full text |Cite
|
Sign up to set email alerts
|

4-Nitroquinoline-1-Oxide-Induced Mutagen Sensitivity and Risk of Nonmelanoma Skin Cancer: A Case–Control Analysis

Abstract: The UV radiation-mimetic chemical 4-nitroquinoline-1-oxide (4-NQO) is thought to induce squamous cell carcinoma (SCC) similar to those induced by UV radiation in animals. Therefore, we tested the hypothesis that cellular sensitivity to 4-NQO is associated with risk of developing skin cancer in a case-control study of 191 patients with nonmelanoma skin cancer (NMSC; 81 SCC and 110 basal cell carcinoma (BCC)) and 176 cancer-free controls. Short-term blood cultures were treated with 4-NQO at a final concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…It was apparent that these risk factors, except for eye color and family history of skin cancer, were associated with a significantly increased risk of CM in this analysis (Table 1). Most of these known risk factors were statistically correlated with each other as expected, similar to what was reported previously for this study population [13]. For example, in 176 control participants, number of sunburns was highly correlated with hair color ( r = 0.191, P = 0.012), eye color ( r = 0.212, P = 0.005), skin color ( r = 0.227, P = 0.003), tanning ability ( r = 0.326, P < 0.001), and freckling in the sun ( r = 0.357, P < 0.001).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…It was apparent that these risk factors, except for eye color and family history of skin cancer, were associated with a significantly increased risk of CM in this analysis (Table 1). Most of these known risk factors were statistically correlated with each other as expected, similar to what was reported previously for this study population [13]. For example, in 176 control participants, number of sunburns was highly correlated with hair color ( r = 0.191, P = 0.012), eye color ( r = 0.212, P = 0.005), skin color ( r = 0.227, P = 0.003), tanning ability ( r = 0.326, P < 0.001), and freckling in the sun ( r = 0.357, P < 0.001).…”
Section: Resultssupporting
confidence: 89%
“…The mutagen sensitivity was expressed as the number of 4-NQO-induced chromatid b/c after cells were treated for 24 h [1113]. Briefly, short-term cultures of 1 ml of fresh whole blood were established in 9 ml of RPMI 1640 medium supplemented with 20 v/v% fetal bovine serum and phytohemagglutinin (Remel, Lenexa, Kansas, USA) at a final concentration of 112.5 µg/ml to stimulate T-lymphocyte growth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent pilot study of the correlation between in vitro BPDE-induced DNA damage and repair (measured by the comet assay) and chromosomal aberrations in primary lymphocytes of 136 cancer-free controls, we found that there was a weak correlation (r = 0.163; P = 0.009) between measurements of Olive tail moment (single DNA strand breaks) and frequencies of chromatid breaks per cell (i.e., mutagen sensitivity) (ref. 25).…”
Section: Discussionmentioning
confidence: 99%
“…Because Dr. T. C. Hsu developed the mutagen sensitivity assay with bleomycin as an effective inducer of chromosomal aberrations in vitro, this assay has been widely used in epidemiologic studies to assess genetic susceptibility to various types of cancer. The assay has been modified with a variety of etiologically related challenge mutagens to evaluate cancer susceptibility in association studies, such as BPDE for tobacco-related cancers of the lung (4,(6)(7)(8) and SCCHN (9-11), g-radiation for glioma (22,23), and UV light or 4-nitroquinoline-1-oxide for skin cancer (24,25). These studies have consistently showed that in vitro induced mutagen sensitivity phenotype is a risk factor for developing cancers.…”
Section: Discussionmentioning
confidence: 99%